Evaluation of the Synergistic Effect of Erosion-Corrosion on AISI 4330 Steel in Saline-Sand Multiphase Flow by Electrochemical and Gravimetric Techniques - Dario Yesid Peña Ballesteros; Yelsin Enrique Mendez Camacho; Lizeth Viviana Barreto Hernandez (International Journal of Electrochemistry)
The synergistic effects of fluid flow, sand particles, and solution pH on erosion-corrosion of AISI 4330 steel alloy in saline-sand medium were studied through a rotating cylinder electrode (RCE) system by weight-loss and electrochemical measurements. The worn surface was analyzed by X-ray diffraction (XRD) and scanning electron microscopy (SEM). Results show that, under all the test conditions assessed, the passivity of the steel alloy could not be maintained; as a result, an activation mechanism dominates the corrosion process of steel alloy. Furthermore, the potentiodynamic curves show that, with the increasing of the electrode flow rate and particle size, the anodic current density increased, which is due to deterioration of the electrode by the impacting slurry. Although the increase of particle size affects the anodic current density, the effect of particle size does not cause a significant change in the polarization behavior of the steel electrode. The electrochemical impedance and potentiodynamic curves suggest that erosion-corrosion phenomenon of the ASISI 4330 steel is under mixed control of mass transport and charge transfer. The inductive loops formed in the impedance plots are representative of an increase in roughness of the electrode caused by the particles impacting at the surface. The change in the passivity of the steel alloy as the pH is altered plays an important role in the corrosion rate.